SYSTEMATIC LITERATURE REVIEW: PROJECT BASED-LEARNING IN ENGLISH LANGUAGE TEACHING - Nur Adilah (Langue (Journal of Language and Education), 2023)
Many different types of study, including Project-Based Learning (PBL) studies conducted in English language teaching areas, have required a systematic review in order to be evaluated. The systematic review's evidence base incorporates the leading research hypotheses as well as empirical information based on subject-matter expertise. The several journal publications about PBL in English language teaching are methodically explained in this review. 13 articles from 1,194,338 from 2019 to 2022 were extracted with the use of three databases—ERIC, Research Gate and Google Scholar—and after taking inclusion and exclusion criteria into consideration. In general, this review is beneficial to teachers because it informs them of the journal papers that can be used to identify PBL research gaps.